Implementation and Effectiveness of The Quran Reading Acceleration Program at SD Negeri 19 Sabang - Muhammad Husien, Istisnawati; Azhar, Azhar; Zubaidah, Zubaidah (Teunuleh Publisher, 2025)
This study explores the implementation and effectiveness of the accelerated Qur'an reading program at SD Negeri 19 Sabang, which has been running since 2012. The program aims to improve students' Qur'anic reading skills, reinforce religious character, and instill Islamic values from an early age. Using a qualitative descriptive approach, data were collected through interviews, observation, and documentation involving teachers, students, school principals, and parents. Findings reveal that the program is implemented systematically through methods such as talaqqi, drilling, and audiovisual aids, integrated into daily learning activities. Most students showed significant progress in reading fluency (fashahah), proper pronunciation (makharijul huruf), and understanding of tajwid rules. The success of the program is supported by teacher commitment, parental involvement, and varied learning methods. However, the study also notes challenges such as inconsistent reading practice among students and differences in initial reading ability. The program proves to be a promising model for holistic religious education, though it requires sustained guidance and support to achieve consistent outcomes.